Perspektif Generasi Z Pada Personal Branding Akun Instagram The Connell Twins - Cantika, Ratna; Yonavilbia , Eka (CV ODIS, 2025)
The Connell Twins are influencers who carry out interesting personal branding activities for Generation Z. The content on The Connell Twins' Instagram account displays lifestyle content that has a negative impact. This study aims to analyze the perspective of Generation Z on personal branding built by The Connell Twins through the Instagram social media platform. Instagram has become one of the main social media used to share visual content. This study uses a qualitative descriptive method and an interview, observation, and documentation approach. This study uses the Use and Effect Theory to understand the impact of social media in shaping lifestyle and self-perception among Generation Z. The results of the study indicate that although The Connell Twins have succeeded in building an iconic and attractive self-image for their followers, there is a risk of negative impacts, especially related to unrealistic lifestyles and cultural norms that are not always in accordance with the social environment of their followers in Indonesia